Advances in bioprocessing for efficient bio manufacture. Issue 65 (16th July 2015) - Zhang, Genlin; Qi, Feng; Jia, Haiyang; Zou, Changling; Li, Chun
<x xml:space="preserve">Abstract</x> The strategies involving molecular, cellular and community levels for improving various bioprocesses are reviewed with specific examples presented.